2016
DOI: 10.2522/ptj.20140611
|View full text |Cite
|
Sign up to set email alerts
|

“Stepping Up” Activity Poststroke: Ankle-Positioned Accelerometer Can Accurately Record Steps During Slow Walking

Abstract: Although not recommended by the manufacturer, positioning the accelerometer at the ankle (compared with the waist) may fill a long-standing need for a readily available device that provides accurate feedback for the altered and slow walking patterns that occur with stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 14 publications
4
66
1
Order By: Relevance
“…The validity and reliability of wearable activity monitors in measuring step counts also appears to be dependent upon the position on the body in which the device is placed. Activity monitors positioned on the ankle appear to be more accurate than wrist-mounted and waist-mounted devices in counting steps, particularly during slow walking conditions [39,42,43]. This may be because larger accelerations occur at the ankle during walking due to the distance from Step count The total step count has excellent test-retest reliability when used for 3 days in individuals with stroke; monitoring for less than a 3-day period is not recommended due to high variability Rett syndrome (27) Home…”
Section: Ankle-worn Devices Provide the Most Accurate Measurement Of mentioning
confidence: 99%
See 1 more Smart Citation
“…The validity and reliability of wearable activity monitors in measuring step counts also appears to be dependent upon the position on the body in which the device is placed. Activity monitors positioned on the ankle appear to be more accurate than wrist-mounted and waist-mounted devices in counting steps, particularly during slow walking conditions [39,42,43]. This may be because larger accelerations occur at the ankle during walking due to the distance from Step count The total step count has excellent test-retest reliability when used for 3 days in individuals with stroke; monitoring for less than a 3-day period is not recommended due to high variability Rett syndrome (27) Home…”
Section: Ankle-worn Devices Provide the Most Accurate Measurement Of mentioning
confidence: 99%
“…Overall the methodological quality of the studies examined was high, with each scoring ≥7. Of the assessed studies, 10 included participants with multiple sclerosis [32][33][34][35][36][37][38][39][40][41], 7 included participants after stroke [32,33,[42][43][44][45][46], 4 included participants with PD [27,33,47,48], 3 included participants with a spinal cord injury [32,49,50], 2 included participants with cerebral palsy [51,52], 2 included participants with a traumatic brain injury [32,42], and participants with Rett syndrome [53] and muscular dystrophy [32] were included in 1 study each. The most frequently used monitors included the StepWatch activity monitor (a biaxial accelerometer) [39,41,42,44,53], the ActiGraph GT3X (a triaxial accelerometer) [35,39,40,50], the SWA (a multisensor device) [46,49,52], and the Digi-Walker pedometer [27,32...…”
Section: Table 2 (Continued)mentioning
confidence: 99%
“…Our study indicated that low physical performance or reduced thigh muscle thickness in stroke patients may be due to less PA during convalescence hospitalization. Measuring PA is often difficult in patients with a very slow speed, such as disabled stroke survivors [16]. Our study results may be useful to identify low PA hospitalized stroke patients, who can then be instructed to increase PA.…”
Section: Discussionmentioning
confidence: 93%
“…The average daily number of steps during the middle 2-day period of the 4 days was used as the index of daily PA [17]. This ankle-attached measurement device is not a standardized method, but it was effective for measuring the number of steps taken by individuals who were unable to walk faster than 0.5 m/s in a recent study [16]. The reliability of the step measurement was also calculated before statistical analyses were performed.…”
Section: Measurement Of Pamentioning
confidence: 99%
See 1 more Smart Citation